Non-readmission decisions in the intensive care unit: A qualitative study of physicians’ experience in a multicentre French study - Jacquier, Marine (PLoS One, 2021)
PURPOSE: Deciding not to re-admit a patient to the intensive care unit (ICU) poses an ethical dilemma for ICU physicians. We aimed to describe and understand the attitudes and perceptions of ICU physicians regarding non-readmission of patients to the ICU. MATERIALS AND METHODS: Multicenter, qualitative study using semi-directed interviews between January and May 2019. All medical staff working full-time in the ICU of five participating centres (two academic and three general, non-academic hospitals) were invited to participate. Participants were asked to describe how they experienced non-readmission decisions in the ICU, and to expand on the manner in which the decision was made, but also on the traceability and timing of the decision. Interviews were recorded, transcribed and analyzed using textual content analysis. RESULTS: In total, 22 physicians participated. Interviews lasted on average 26±7 minutes. There were 14 men and 8 women, average age was 35±9 years, and average length of ICU experience was 7±5 years. The majority of respondents said that they regretted that the question of non-readmission was not addressed before the initial ICU admission. They acknowledged that the ICU stay did lead to more thorough contemplation of the overall goals of care. Multidisciplinary team meetings could help to anticipate the question of readmission within the patient’s care pathway. Participants reported that there is a culture of collegial decision-making in the ICU, although the involvement of patients, families and other healthcare professionals in this process is not systematic. The timing and traceability of non-readmission decisions are heterogeneous. CONCLUSIONS: Non-readmission decisions are a major issue that raises ethical questions surrounding the fact that there is no discussion of the patient’s goals of care in advance. Better anticipation, and better communication with the patients, families and other healthcare providers are suggested as areas that could be targeted for improvement.